Transverse deflecting structure XFEL TDS INJ. (September 2016) - Volobuev, E N; Zavadtsev, A A; Zavadtsev, D A; Kravchuk, L V; Paramonov, V V; Lalayan, M V; Smirnov, A J; Sobenin, N P; Churanov, D V
Abstract: The Transverse Deflecting System XFEL TDS System INJ has been built as the part of the European X-ray Free Electron Laser for longitudinal bunch profile and slice emittance measurements. The 0.7 long Transverse Deflecting Structure (TDS), as the part of the system, has been built on base of the disk-loaded structure with hybrid EH-wave, operating frequency 2997.2 MHz and pulse input RF power up to 3 MW. The structure has been built, tuned and installed in the XFEL Injector beam line. All design parameters have been got at low RF power level. Electron beam has been passed through the whole Injector including TDS.